PANDANGAN MUI KOTA MEDAN TERHADAP PENYIMPANGAN AQIDAH ISLAM DALAM MASYARAKAT - Indra Harahap; Salahuddin Harahap; Nisa Idriani Lubis (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
The purpose of this thesis research is to find out the view of Medan MUI on the Deviations of Islamic Aqeedah in Society, this study uses the Phenomenology method in the form of understanding, examples and phenomenological methods.  which is consciously and individually experienced by a group of individuals in his life.  With the connection with the deviation of Islamic Aqeedah in society in the city of Medan. Related to the issues that will be discussed in this Journal, Medan MUI believes that the deviation of the Islamic Aqeedah is an issue that is in contact with the principles in Islamic teachings.  Because of that, aqeedah requires unity which is the main understanding in the faith. The touching is against and contradicting the basics that have been qath'i in Islamic teachings, for example related to faith and others.Keywords: Deviations, Islamic Aqeedah, MUI Medan City.